Medical education program restructuring according to the PUIGEP (prevalence, urgency, possible intervention, gravity, exemplarity, prevention) system - Amer Sebaaly; Mohammad Daher; Lynn Abdo; Cesar Yaghi; Elie Nemr; Gaby Kreichati (BMC Medical Education)
Abstract Introduction The evolution of the academic curriculum in medical school presents opportunities and challenges. The Bologna process has divided medical training into 3 cycles (License, Master, Doctorate), with each cycle assigned a number of credits. The aim of this work is to distribute the 120 credits of the curriculum equitably between its various modules, using an objective method that takes into account students’ workload and study time. Materials and methods The curriculum credit allocation process involved an assessment of chapter relevance using a PUIGEP-MG (Prevalence, Urgency, possible Intervention, Gravity, Exemplarity, Prevention) questionnaire, as well as an assessment of workload by the students. Chapters were then weighted according to relevance and workload, and credits were distributed proportionally. This process ensured a balanced distribution of credits while considering the students’ needs and the clinical importance of the chapters. Results The results reveal that of 437 chapters spread over 26 modules, the majority were judged “Essential” (48.8%) or “Indispensable” (32.5%) in terms of relevance. 8.4% of the courses were eliminated or transferred. The workload was distributed equitably, with significant differences between 4th and 5th year courses mainly in the proportion of heavy workload (17% in 4th year vs. 2% in 5th year; p < 0.001) and in the average course weight (1.24 in 4th year vs. 1.14 in 5th year; p = 0.04). Credits were allocated according to chapter weight, with some modules receiving more than 6 credits. A grouping of subjects was proposed to balance the number of credits between semesters. Conclusion In conclusion, this study developed an objective framework for weighting medical courses, and aligning credit distribution with relevance and student workload. Furthermore. it optimized curriculum design by balancing semester loads, prioritizing general practice, and eliminating less pertinent courses. While innovative, limitations like unvalidated metrics invite future research to refine and enhance medical education frameworks.